2019
DOI: 10.1159/000496475
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chronic Obstructive Pulmonary Disease and Dementia: Systematic Review and Meta-Analysis of Cohort Studies

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a common disease among the elderly, which has been linked to cognitive decline. However, the relationship between COPD and dementia remains unclear. Summary: We conducted a systematic literature review by searching databases such as Pubmed, Embase, EBSCO, and Cochrane Library (from inception to April 18, 2018) for studies on COPD that also investigated the prevalence of dementia. We found 3 cohort studies including a total of 39,392 COPD patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Potential reasons can be further explored in future studies. Consistent with many studies, a higher prevalence of dementia and AD was seen in patients with COPD (29)(30)(31).…”
Section: Discussionsupporting
confidence: 88%
“…Potential reasons can be further explored in future studies. Consistent with many studies, a higher prevalence of dementia and AD was seen in patients with COPD (29)(30)(31).…”
Section: Discussionsupporting
confidence: 88%
“…The major pain (0.17) associated with AD is joint pain (0.15), such as arthritis (0.20) and headaches (0.22), such as migraines (0.12), but not with skin pain (0.00); not with stomach pain (0.00), such as ulcers (0.03); not with mouth pain (0.00), such as caries (0.02); and not with back pain (0.06). Finally, lung diseases, and in particular COPD (0.09) [ 39 ], and asthma (0.09) have been associated with AD [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the relationship between cognitive function and pulmonary function, previous studies reported a correlation between decreased pulmonary function and impaired cognitive function in COPD patients, and these studies mostly targeted FEV 1 as a predictor (Dodd et al., 2010, Wang et al., 2019). Community-based studies also reported a correlation between pulmonary function and cognitive function (Emery et al., 2012, Richards et al., 2005).…”
Section: Discussionmentioning
confidence: 99%